2012
DOI: 10.1590/s0103-21002012000500020
|View full text |Cite
|
Sign up to set email alerts
|

Diretrizes brasileiras de hipertensão arterial: realidade da enfermagem em hospital especializado

Abstract: Objective: To evaluate knowledge about the technique of blood pressure measurement among nursing professionals in a health care institution. To identify the relationship between professional qualification and the proper development of technique. Methods: The researcher applied a questionnaire to nursing professionals during the verification of arterial pressure of patients. These questions related to the Brazilian Guidelines on Arterial Hypertension V. Results: Of the nursing professionals, technicians and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
2
0
10
Order By: Relevance
“…With regard to using cuff proportional to the circumference of the arm of the patient, study showed that of 107 professionals observed regarding the Scouting of the BP in a Center specializing in cardiology, all used the cuff with standardized size, including for obese clients and thin. 5 The question addresses the instrument 06 customer preparation before measurement of the BP, which includes checking that it is not with a full bladder, not practiced physical exercises in the past 30-90 min, not ingested alcoholic beverages, coffee, food or smoked until 30 min prior to measurement (1) . When evaluated all the necessary actions to be performed by the professional in relation to the preparation of the patient, no professional had questioned whether the client had emptied his bladder before the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to using cuff proportional to the circumference of the arm of the patient, study showed that of 107 professionals observed regarding the Scouting of the BP in a Center specializing in cardiology, all used the cuff with standardized size, including for obese clients and thin. 5 The question addresses the instrument 06 customer preparation before measurement of the BP, which includes checking that it is not with a full bladder, not practiced physical exercises in the past 30-90 min, not ingested alcoholic beverages, coffee, food or smoked until 30 min prior to measurement (1) . When evaluated all the necessary actions to be performed by the professional in relation to the preparation of the patient, no professional had questioned whether the client had emptied his bladder before the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…When evaluated all the necessary actions to be performed by the professional in relation to the preparation of the patient, no professional had questioned whether the client had emptied his bladder before the procedure. 5 The indirect method with the auscultatory technique is the most widely used resource for blood pressure measurement. However, it is essential previously measure the systolic blood pressure by palpation in order to avoid excessive cuff inflation and the Tibúrcio MP, Melo GSM, Balduíno LSC et al…”
Section: Resultsmentioning
confidence: 99%
“…Esse desfecho deve-se à qualidade da formação profissional (considerando-se a carga horária do curso). 17 Entre as sugestões de cunho educativo para resolução de problemas da área da saúde, estudiosos da área propõem o uso de uma hipermídia educacional para o ensino da técnica de medida de PA. A ferramenta apresenta vídeos, fotos, animações e simulações para demonstrar e ensinar o procedimento. 18 De acordo com os resultados deste estudo, uma das áreas críticas a serem abordadas em processo educativo seria a questão da comunicação entre o profissional de saúde e o paciente.…”
Section: Discussionunclassified
“…Estudos 18,19 realizados com profissionais de instituições de saúde para avaliar o conhecimento sobre a técnica de verificação da pressão arterial, nenhum profissional acertou a questão relacionada ao tamanho do manguito a ser utilizado, assim como não realizou a medida da CB antes da aferição da PA. Outra pesquisa 13 também observou que a utilização inadequada do manguito em relação as suas proporções (comprimento x largura) e a circunferência braquial durante a medida da PA pode estar relacionado com lacunas no conhecimento dos profissionais da saúde em relação à técnica da medida da PA e à utilização do manguito ideal, tendo em vista que, há no local da pesquisa manguitos de diferentes dimensões.…”
Section: Discussionunclassified
“…Em pleno século 21, a largura de 12 cm proposta pelo médico alemão permanece como referência padrão. Observa-se um crescimento no número de estudos que envolvem erros da medida da PA atribuídos aos instrumentos, examinadores e examinados 5,9,13 . Em estudo 5 , evidenciou-se que dentre as etapas do procedimento da medida indireta da PA, a menos realizada entre os indivíduos estudados foi a seleção do manguito apropriado, pois apenas 7% dos indivíduos preocuparam-se com esta etapa.…”
Section: Introductionunclassified